2000
DOI: 10.1016/s0092-8674(00)00069-6
|View full text |Cite
|
Sign up to set email alerts
|

The 4 Å X-Ray Structure of a Tubulin:Stathmin-like Domain Complex

Abstract: Phosphoproteins of the stathmin family interact with the alphabeta tubulin heterodimer (tubulin) and hence interfere with microtubule dynamics. The structure of the complex of GDP-tubulin with the stathmin-like domain of the neural protein RB3 reveals a head-to-tail assembly of two tubulins with a 91-residue RB3 alpha helix in which each copy of an internal duplicated sequence interacts with a different tubulin. As a result of the relative orientations adopted by tubulins and by their alpha and beta subunits, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
258
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(277 citation statements)
references
References 41 publications
13
258
1
1
Order By: Relevance
“…This is likely mediated predominantly by stress-activated JNK signaling as JNK inhibition substantially reduces OS-induced phosphorylation at that site (14). The STMN Ser-38 residue is located in a disordered linker region that does not interact with tubulin (39), and prior in vitro studies have suggested that Ser-38 phosphorylation had marginal effects in on STMN-tubulin binding and microtubule-destabilizing activity (11,28), which were confirmed by our current investigations (Fig. 9H).…”
Section: Discussionsupporting
confidence: 91%
“…This is likely mediated predominantly by stress-activated JNK signaling as JNK inhibition substantially reduces OS-induced phosphorylation at that site (14). The STMN Ser-38 residue is located in a disordered linker region that does not interact with tubulin (39), and prior in vitro studies have suggested that Ser-38 phosphorylation had marginal effects in on STMN-tubulin binding and microtubule-destabilizing activity (11,28), which were confirmed by our current investigations (Fig. 9H).…”
Section: Discussionsupporting
confidence: 91%
“…of C␣ positions: 0.8 Å, within the range expected for identical structures, given the resolution of the corresponding diffraction data]. Therefore, the main function of the RB3-SLD C-terminal helix is to hold tubulin heterodimers together in T 2 R in relative orientations that are consistent with low resolution images of curved tubulin assemblies that do not comprise RB3-SLD and are obtained with or without colchicine (20). We summarize here the movements within subunits that give rise to the subunits orientation changes on going from a curved to a straight assembly.…”
Section: Discussionsupporting
confidence: 53%
“…2 A). The RB3-SLD C-terminal helix only contacts residues in the nucleotide binding domain and in the C-terminal helical hairpin (20), an ensemble that is unchanged in T 2 R with respect to straight protofilaments [root mean square deviation (r.m.s.d.) of C␣ positions: 0.8 Å, within the range expected for identical structures, given the resolution of the corresponding diffraction data].…”
Section: Discussionmentioning
confidence: 99%
“…5). Although SulA has no sequence homologues in eukaryotes, a similar mechanism is seen with the tubulin-binding protein stathmin, which sequesters tubulin dimers, although it disrupts lateral interactions between protofilaments rather than acting via the T7 loop to affect interactions within the protofilament (35). The second effect of SulA is binding to preformed FtsZ filaments.…”
Section: Resultsmentioning
confidence: 99%